Strategy of Strengthening Character Education Based on Al-Quran Surah Lukman; 12-19 in SMP Muhammadiyah 2 Taman - Elly Elvina Sahara; Yayuk Fauziyah; Eni Fariyatul Fahyuni (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2019)
This paper discusses the importance of strategies to Strengthen student character education based on Qs. Lukman verses 12-19. Education is a human activity that has the intention of developing individuals in totality in accordance with Reviews their potential and competence. Therefore, education Becomes the obligation and responsibility of parents (families), schools and communities so as to create a quality generation that is a generation of strong faith, broad knowledge and understanding, good social charity and noble character, a reflection of personal character with the desire of the people. This paper uses a descriptive qualitative approach that seeks to explain the form of strategies for strengthening character education based on Qs. Lukman verses 12-19. Keywords: Strategy and Character Education